PERBANDINGAN KUALITAS CITRA HARD COPY DENGAN HASIL DIGITIZER DAN KAMERA SAKU PADA FOTO POLOS FRAKTUR TULANG EKSTREMITAS ATAS DI BAGIAN RADIOLOGI RSUP DR. SARDJITO - , RIZZA MAULANA AZMI, Dr. dr. Lina Choridah, Sp.Rad(K) ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background : Fracture of upper extremity is an emergency situation which need a quick treatment. The diagnose could be done by running a supporting examination, which is radiology. Indonesia only have for about 700 radiologist which distributed unevenly, therefore teleradiology is needed. Teleradiology needs an imaging device which could produce a good quality image, so there will be no misinterpretation on the reading process. Objective : Understanding the quality differences and diagnose of hard copy film and soft copy file of digitizer and pocket camera of plain upper extremity fracture x-ray. Method and Material : This is an observational research, using 34 samples of plain upper extremity fracture x-ray. The digital data from work station is being printed using a laser printer into hard copy form, then the hard copy film is being digitalized using digitizer and pocket camera. The image quality of soft copy files of digitizer and pocket camera are being compared with the hard copy. Result : There were no significant differences of image quality among hard copy film and soft copy file of digitizer (p=1.000), buat there were significant differences among hard copy film and soft copy file of pocket camera (p=0.000). There were no significant differences of diagnose among hard copy film and soft copy file of digitizer and pocket camera (p=1.000). Conclusion : Image quality of soft copy file of digitizer is equal with hard copy film quality, and hard copy film image quality is better than soft copy file of pocket camera. The diagnose of the three sample groups have uniformity.